Death of a cookbook author - Hollis, Lee (Hollis, Lee. Hayley Powell food and cocktails mystery., 2018)
When Hayley Powell<U+2019>s idol, cookbook author and TV personality Penelope Janice, invites her to participate in a Fourth of July celebrity cook-off at her seaside estate in Seal Harbor, Maine, Hayley couldn<U+2019>t be more flattered. She just hopes she can measure up. With a who<U+2019>s who of famous chefs whipping up their signature dishes, this holiday weekend has all the ingredients for a once-in-a-lifetime culinary experience. Instead, Hayley gets food poisoning her first night and thinks she overhears two people cooking up a murder plot. The next morning, a body is found at the bottom of a cliff. Tragic accident or foul play? To solve a real cliffhanger, Hayley will need to uncover some simmering secrets<U+2014>before a killer boils over again . . .